Effect of omeprazole and sucralfate on gastrointestinal injury in a fasting/NSAID model. (9th November 2021) - Bishop, Rebecca C.; Kemper, Ann M.; Wilkins, Pamela A.; McCoy, Annette M.
Summary: Background: Equine gastric ulcer syndrome (EGUS) is a common and significant cause of morbidity in horses, with a range of clinical signs, including inappetence, colic and poor performance. Hospitalised horses are exposed to factors that may induce EGUS, including fasting and nonsteroidal anti‐inflammatory drug (NSAID) administration, and may be at risk for development of squamous (ESGD) and glandular gastric disease (EGGD). Prophylactic anti‐ulcer medication is often prescribed for these patients, but drug selection is complicated by different aetiology and response to treatment of ESGD and EGGD. Objectives: To establish the efficacy of sucralfate or omeprazole used prophylactically in horses exposed to a combined feed‐fast and NSAID administration EGUS induction protocol. We hypothesised that these drugs would be equally effective for prevention of gastric lesions in the experimental cohort. Study design: Randomised crossover experimental design. Methods: Horses ( n = 14) received either omeprazole (1 mg/kg PO q24h) or sucralfate (20 mg/kg PO q8h) while undergoing the feed‐fast/NSAID protocol, allowed an 8‐week washout period, and then administered the alternate treatment. Serial gastroscopy, ultrasound and haematology documented treatment effects. Results: ESGD and EGGD score increased over time under both treatments. There was a significant effect of treatment on EGGD scores ( P < .001), with post‐treatment EGGD scores higher for horses receiving sucralfate (median 3; IQR 2.25, 3) than omeprazole (1; 1, 1). The effect of treatment on ESGD scores just achieved significance ( P = .05), with post‐treatment ESGD scores higher for sucralfate (4; 3, 4) than omeprazole (2; 2, 3). Main limitations: This study was performed in healthy horses, and response to treatment may differ in horses with clinical illness. Additional investigation in a larger population may be required to detect significant differences in other clinical parameters. Conclusions: Omeprazole was superior to sucralfate for mitigating gastric lesion severity in healthy horses exposed to a feed‐fast/NSAID model.